Evaluation of streambank stabilization structures on upstream and downstream bank erosion - Monzon, Corben Christopher (Kansas State University, 2024)
For many decades streambank stabilization techniques have been used to help reduce channel erosion and restore fluvial systems to a more natural state. The overarching goal of this research is to better understand how river systems respond to streambank stabilization (SBS). In this case study, the aim is to broaden the understanding of the effects of SBS projects from a localized scale to a reach, in hopes of answering the research question: Do SBS projects reduce the net amount of sediment that is carried by the river, or do they push the ‘erosion problem’ upstream or downstream? To evaluate this question, a before-after construction analysis was established to examine changes in channel geometry along two reaches of the Cottonwood River, located in east-central Kansas, USA. Each reach consists of three meanders, with the middle meander containing a SBS project of rock vanes, toe rock, and bank shaping. The remaining two meanders, located upstream and downstream of the SBS project, remained unmodified. Over the past six years, these study reaches have been surveyed five to six times, with the majority of the topographic surveys occurring prior to construction. To further the understanding of the measured changes in channel geometry, a collection of channel topographic data, along with USGS stream gage data, was used to simulate flows using HEC-RAS modeling. The results from these analyses indicate (1) streambank lateral retreat rates and stream power were reduced at the stabilized sites, (2) streambank erosion and stream power increased upstream and downstream of the stabilized sites, and (3) the reaches had a net streambed deposition following construction. Overall, more monitoring is necessary to determine the long-term impacts of SBS and whether the aforementioned results are attributed to a “break in” period or a new trend.
Keywords: Streambank; Stabilization; Erosion; Streambed; HECRAS; Modeling